Sorption and Desorption of Diuron, Hexazinone and Mix (Diuron + Hexazinone) in Soils With Different Attributes - SOUSA,G.V. (2018)
ABSTRACT: In Brazil, sugarcane is grown in large areas. Weed control in sugarcane fields is done by chemical method, since it is more efficient and less expensive. In this method, herbicides that persist in the environment for long periods are used, among which there are hexazinone and diuron, which are applied in mixtures marketed by the industry. This research evaluated the sorption and desorption of hexazinone and diuron applied alone and in mixture, in two samples of Red-Yellow Latosols (LVAG and LVAV) and a Organosol (OR), with and without manure. Sorption isotherms were built using the batch equilibrium method and the identification and quantification of herbicides was obtained through a high-performance liquid chromatography (HPLC) with UV-Vis detector. There were high diuron sorption coefficients (Kf) in the soils. The hexazinone Kf values found were low in LVAG and LVAV soils, and they were high ground only in OR. In all soils, diuron and hexazinone showed higher Kf values when mixed. There was a direct relation between the addition of manure to the substrate and the Kf values . Higher desorption values (Kfd) in relation to those of sorption in LVAG and LVAV soils indicate gradual release of these herbicides in the soil solution when using organic fertilizer, showing increased sorption and desorption of these molecules; this is accentuated when they are mixed. In the Organosol, desorption was very low, and cannot be quantitated by the used method. It is possible to conclude that the incubation of LVAG and LVAV soil with manure helps both the process of sorption and desorption of herbicides. However, sorption and desorption in the Organosol is high indicating very low agrochemicals such strong bonds with soil colloids.